The tragic and hidden face of modern victimism.: Rethinking the unthinkable condition of a new way of being a victim - Noudjom Tchana, Alban Pascal de (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
A significant majority of private and public institutions is today marked by the scandal of sexual abuse. The media flood about these scandals spares no organization, be it governmental, non-governmental, religious or political. There are thousands of victims. Unfortunately, around these unacceptable abuses is born a new type of marketing that folklorizes the pain and transforms it into business. We are witnessing the rise of a new class of victim and a new way of being a victim. It is a subtle victimism that is at issue here, the very one who sees the condition of victim as an advantageous situation from which one can derive great profits. The following discussion explores the question of victimisme as well as its challenges in the Catholic Church and in a trend of contemporary feminism.